2010
DOI: 10.1055/s-0029-1246216
|View full text |Cite
|
Sign up to set email alerts
|

Direct Costs for Care and Glycaemic Control in Patients with Type 2 Diabetes in Sudan

Abstract: The aim of this study was to estimate the contribution by type 2 diabetic patients in a low-income country from their own income in attempting to control the disease and to prevent chronic diabetes complications through good glycaemic control. Socio-economic and demographic data for study subjects were obtained from 822 adult diabetic patients attending public or private diabetic clinics in Khartoum State, Sudan. The average annual income of diabetic patients was estimated as USD 1.923. The direct cost of diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 11 publications
1
38
0
Order By: Relevance
“…Another example is a recent study from Iran in 2009, which gave an annual cost figure of US$ 152 per DM patient [9]. Similarly, in Tunisia, an analysis in 1994 estimated an annual cost figure as low as US$ 117 [10], in Egypt costs were even lower [11] and a recent study in Sudan showed direct costs to amount USD 175 per year [12]. Middle income countries, such as those in Latin America and the Caribbean region, tend to be in-between Western and developing countries [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is a recent study from Iran in 2009, which gave an annual cost figure of US$ 152 per DM patient [9]. Similarly, in Tunisia, an analysis in 1994 estimated an annual cost figure as low as US$ 117 [10], in Egypt costs were even lower [11] and a recent study in Sudan showed direct costs to amount USD 175 per year [12]. Middle income countries, such as those in Latin America and the Caribbean region, tend to be in-between Western and developing countries [22].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, with only three studies from countries in the region (Iran, Tunisia and Egypt) there is a dearth of information on the economic impact of DM in the Middle East [9-12], especially the Arabian Peninsula, where no specific studies were carried out. WHO estimates for the per capita expenditure on health care in the region amounted to US$ 497 for UAE during 2004 [13].…”
Section: Introductionmentioning
confidence: 99%
“…The estimated annual direct cost of treating diabetes across private and public clinics in Khartoum, for instance, has been estimated to be US$175, which is equivalent to about 9% of the annual wage of a patient with diabetes in this setting 21. The cost burden to the patient for the treatment of severe diabetic foot ulcer is equivalent to about 2.1 years of average annual income in Tanzania, against 0.8 years in the USA 22.…”
Section: Economic Burden Of Diabetes Mellitus In Africamentioning
confidence: 99%
“…The reasons for poor adherence are multifaceted and complex, and include, Patient-centered factors (such as age, sex, education, and forgetfulness), therapy-related factors (such as treatment complexity and side effects), healthcare system factors (such as drug availability and accessibility to healthcare), social and economic factors (such as cost of therapy, income and social support) [10]- [12]. In Sudan 77% were found to be uncontrolled due to cost related factors [13].…”
Section: Introductionmentioning
confidence: 99%